Promoting physical activity in hospitalized patients with mild ischemic stroke: a pilot study. Issue 4 (19th May 2017) - Kanai, Masashi; Nozoe, Masafumi; Izawa, Kazuhiro P.; Takeuchi, Yuka; Kubo, Hiroki; Mase, Kyoshi; Shimada, Shinichi
Abstract: Background: Patients with acute stroke spend most of their hospital day inactive. However, a method to promote physical activity (PA) in stroke has not been established. Objective: To evaluate the effectiveness of promoting PA by enhancing self-efficacy in hospitalized patients with mild ischemic stroke. Design: Pre–post interventional study. Methods: Hospitalized patients with mild ischemic stroke who could walk without assistance were recruited. We measured the daily number of steps taken as the index of daily hospitalized PA using an accelerometer. At the baseline measurement, patients did not receive accelerometer-based feedback. To promote hospitalized PA, a physical therapist provided instruction on the self-monitoring approach and discussed PA targets, encouraged the patients to walk more, and instructed them on the importance of PA after stroke. We also measured self-efficacy for PA using an assessment tool at the baseline and during the intervention. Results: Twenty-two patients (62.5 years old, 68.2% men) were included. PA during the intervention was higher than that at the baseline measurement (5709.4 ± 2236.1 vs. 2813.9 ± 1511.9 steps/day, p < 0.001). Self-efficacy for PA during the intervention was also higher than that at the baseline measurement (76.4 ± 18.8 vs. 58.9 ± 29.0 points, p < 0.001). Conclusions: Promoting PA by enhancing self-efficacy may increase PA and self-efficacy for PA in hospitalized patients with mild ischemic stroke. The present results might provide new strategies of PA promotion in these hospitalized patients.